Adopsi Nilai Kearifan Lokal dalam Kinerja Kepolisan Daerah Provinsi Lampung - Simon Sumanjoyo Hutagalung (Universitas Merdeka Malang, 2018)
In order to optimizing its performance, regional police of Lampung used cultural approach as a problem solving. This research intend to analyze how is the performance of regional police Lampung with the presence of that adoption and describe the stages of adoption of local wisdom. The type of this research is descriptive research with qualitative approach. The primary data was collected from the result of interview and observation, while the secondary data was collected from documents such as the decree of featured programs by the chief of regional police Lampung which included program that has been adopted from local wisdom of Lampung. The researcher has found the stages of adoption of local wisdom in the performance of regional police Lampung; a) Awareness stage, b) Interest stage, c) Assessment stage, d) Eksperiment stage, and e) Adoption stage. However, the performance of regional police Lampung considered good enough and quite able to decreasethe number of crimes in Lampung, although they are still working hard to optimalize the process of reducing a crime in Lampung.DOI: https://doi.org/10.26905/pjiap.v3i1.1923